Relationship between prenatal and postnatal conditions and accelerated postnatal growth. Impact on the rigidity of the arterial wall and obesity in childhood. (August 2019) - Mora-Urda, A. I.; Acevedo, P.; Montero López, M. P.
Abstract: Restricted growth in utero and accelerated postnatal growth (APG) in the postnatal period have been associated with the development of overweight, obesity and an increased cardiovascular risk in childhood. The objectives of this study were to evaluate the influence of prenatal and perinatal conditions on APG and to evaluate the influence of this APG on different cardiovascular risk factors such as body mass index (BMI), body fat mass index (FMI), blood pressure (BP) and arterial wall stiffness [carotid to femoral pulse wave velocity (cf-PWV)]. All measurements were performed in 355 children (185 boys and 170 girls; 8–11 years). Data on mother weight before and during pregnancy, gestational age (weeks), birth weight (g) and breastfeeding of children were obtained through interviews with families. Children who presented APG were born of mothers with lower BMIs before pregnancy and who gained less weight during the second trimester of pregnancy. They also have a lower gestational age and birth weight, a shorter duration of breastfeeding and a longer duration of artificial feeding (AF). Later in childhood, they had higher values of cf-PWV, BMI, FMI and higher prevalence of hypertension. Low maternal gestational weight gain, inadequate fetal development (low birth weight, shorter gestational age) and reduced breastfeeding duration favor APG. Infants with such APG had higher values of cf-PWV, BP, BMI and FMI later in childhood, along with a higher risk of hypertension and obesity. The interaction between APG and a longer duration of AF had a negative effect on cf-PWV (arterial stiffness) and FMI.